Comparing the effectiveness of different displays in enhancing illusions of self-movement (vection) - Riecke, Bernhard E.; Jordan, Jacqueline D. (Frontiers in Psychology, 2015)
Illusion of self-movement (vection) is used in Virtual Reality (VR) to give users the feeling that they are moving when physical movement is unfeasible. While there has been investigation into which parameters of a VR display may influence vection, it is unknown as to how vection may be influenced by the display itself. Here, we conducted three experiments to determine if there is a difference in vection intensity and onset time between displays. The influence of field of view (FOV) was also analyzed in one experiment. Participants navigated down linear and curvilinear paths in the virtual environment, recorded vection onset time, and rated vection intensity at the end of each trial. User opinions on immersion, motion sickness, vection, and overall preference were recorded retrospectively and compared between the two displays. Repeated-measures ANOVAs revealed no main effect of display in any of the experiments. Furthermore, there was an influence of FOV on vection onset time only. Motion sickness ratings were correlated with mean participant vection intensity to find that mean vection intensity does not predict motion sickness levels. It was concluded that vection is tolerant towards changes in display type, and that vection research in VR won't be confounded by display
Keywords: DG2019; NSERC DG 2026; Riecke; Riecke_2015; VIMS; bernhard-riecke; jacqueline-jordan; journalPaper; vection; vection methods